The Applying Of The Romanowski Test For Identification Of Data Affected By Errors - Milosan, Ioan (European Scientific Journal, ESJ, 2016)
The paper presents an example of calculation to identify data affected by aberrant errors and removing these data from the values of elongation (A) and impact strength (KC) of Ni-Cu austempered ductile iron, by applying the Romanowski tests. All accepted values as fair were noted with the Yes and all values affected by errors were noted with No. This test has identified two aberrant errors of the experimental data. In this way, the experimental results obtained are validated with a statistical confidence level of 95%.